PENINGKATAN KEMANDIRIAN LANSIA DENGAN SENAM LANSIA DI PANTI WERDHA WELAS ASIH SINGAPARNA TASIKMALAYA - jajuk kusumawaty kusumawaty; Dedi Supriadi; Adi Nurapandi; Heni Marliany; Lilis Lismayanti; Ima Sukmawati (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Abstract The elderly experience a decrease in physiological and cognitive functions so that they are vulnerable to various health problems. The health burden of the elderly comes from diseases such as heart disease, stroke, visual impairment and hearing loss. The purpose of the community service is to find out the differences in the level of independence in the Activity of Daily Living (ADL) for the elderly at the Singaparna Werdha Welas Asih Home and to increase independence with gymnastics for the elderly. Methods: (i) Identification of the Level of Independence of the Elderly with the Katz Index (ii) Socialization, and (iii) Evaluation. Results: The number of elderly who took part in community service activities was 20 people. From the activity evaluation, it was found that the elderly were able to understand the material provided and do elderly exercise enthusiastically. Conclusion: The benefits of having knowledge and understanding about increasing the independence of the elderly with elderly exercise are very helpful in improving the health and life expectancy of the elderly Keywords: elderly independence, elderly gymnastics